Active tuning of the vibration band gap characteristics of periodic laminated composite metamaterial beams. (April 2020) - Ren, Tao; Liu, Chunchuan; Li, Fengming; Zhang, Chuanzeng
A novel strategy is proposed to investigate the vibration band-gap and active tuning characteristics of the laminated composite metamaterial beams. The piezoelectric actuator/sensor pairs are periodically placed along the laminated composite beam axis so that the vibration frequency band-gap and active tuning characteristics can be induced. The dynamic equations of the laminated composite metamaterial beams bonded by the piezoelectric actuator/sensor pairs are established based on the Euler–Bernoulli beam theory. The negative proportional feedback control strategy is employed to provide the positive active control stiffness for the piezoelectric actuator/sensor patches. The spectral element method is used to calculate the dynamic responses of the laminated composite metamaterial beams with the periodically placed piezoelectric patches, and the calculation accuracy for the dynamic responses is validated by the finite element method. The results demonstrating the high-performance vibration band-gap properties in the low-frequency ranges can be achieved by properly designing the sizes and the number of the piezoelectric patches. Moreover, the vibration band-gap characteristics, especially the band-gap width and the normalized band-gap width with respect to the considered excitation frequency range, can be significantly changed by tuning the structural parameters of the piezoelectric actuators and sensors. In addition, the cross-ply angle of the laminated composite metamaterial beams has significant influences on the band-gap characteristics and the vibration reduction performance of the laminated composite beam structures.